SEVIRI PrePro: A novel software tool for the pre-processing of SEVIRI geostationary orbit EO data products. (August 2016) - Petropoulos, George P.; Anagnostopoulos, Vasileios
Abstract: The Spinning Enhanced Visible and Infrared Imager (SEVIRI) is a geostationary orbit multispectral sensor on-board the Meteosat second Generation (MSG) platform, acquiring Earth Observation (EO) data over Earth's land surface from the optical to infrared parts of electromagnetic spectrum every 15 min. From the sensor a series of operational products are also provided to the user's community at no cost via EUMETSAT or LSA SAF portals. Herein, an open access stand-alone software product developed in Java programming language is presented for automating key pre-processing steps to all the SEVIRI operationally distributed products. The software tool, named Seviri PrePro, makes use of present day multi-core processors and is able to process very large datasets in a short time period, making it appropriate as well for use in a High Performance Computing (HPC) environment. The practical usefulness of the toolkit is also demonstrated herein using as a case study the SEVIRI evapotranspiration (ET) product. The development of SEVIRI PrePro is of significant importance to the SEVIRI users' community and is also very timely given that, to our knowledge, no similar software tool is freely distributed at present. Its use is anticipated to make a significant contribution to a large number of practical applications requiring use of SEVIRI data, including but not limited, weather forecasting and global climate monitoring at a range of geographical scales. Highlights: First open access software tool for the pre-processing of SEVIRI operational products. A robust validation of a SEVIRI product is demonstrated using our software tool. Software tool is expected to contribute significantly towards the use of geostationary orbit data and operational products in many practical applications.